Performance degradation of direct formic acid fuel cell incorporating a Pd anode catalyst - Jung, Won Suk; Han, Jonghee; Yoon, Sung Pil; Nam, Suk Woo; Lim, Tae-Hoon; Hong, Seong-Ahn (ELSEVIER SCIENCE BV, 2011)
Electrochemical and physical analysis is employed to verify the performance degradation mechanism in direct formic acid fuel cells (DFAFCs). The power density of a single cell measured at 200 mA cm(-2) decreases by 40% after 11 h of operation. The performance of the single cell is partly recovered however, by a reactivation process. Various analytical methods such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), and electrochemical impedance spectroscopy (EIS) are used to investigate the mechanism of performance degradation. The analytical results show that the electrolyte membranes in the DFAFC are stable for 11 h of operation after the reactivation process. The major factors causing performance degradation in the DFAFC are an increment in the anode charge-transfer resistance and a growth in the particle size of the Pd anode catalyst. The anode charge-transfer resistance, confirmed by EIS, increases with operation time and is due to poisoning of the catalyst surface. Although it is not clear what chemical species poisons the catalyst surface, the catalyst surface is cleaned by the reactivation process. Performance losses caused by surface poisoning are completely recovered by the reactivation process. Increase in catalyst size induces a reduction in active surface area, and the performance loss caused by the growth in catalyst size cannot be recovered by the reactivation process. (C) 2011 Published by Elsevier B.V.
Keywords: PALLADIUM; ELECTROOXIDATION; OXIDATION; NANOPARTICLES; METHANOL; OPERATION; ELECTRODE; PTPB; DMFC